Glycation Interferes with the Activity of the Bi-Functional UDP-N-Acetylglucosamine 2-Epimerase/N-Acetyl-mannosamine Kinase (GNE) - Vanessa Hagenhaus; Jacob L. Gorenflos López; Rebecca Rosenstengel; Carolin Neu; Christian P. R. Hackenberger; Arif Celik; Klara Weinert; Mai-Binh Nguyen; Kaya Bork; Rüdiger Horstkorte; Astrid Gesper (Biomolecules, 2023)
Mutations in the gene coding for the bi-functional UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase (GNE), the key enzyme of the sialic acid biosynthesis, are responsible for autosomal-recessive GNE myopathy (GNEM). GNEM is an adult-onset disease with a yet unknown exact pathophysiology. Since the protein appears to work adequately for a certain period of time even though the mutation is already present, other effects appear to influence the onset and progression of the disease. In this study, we want to investigate whether the late onset of GNEM is based on an age-related effect, e.g., the accumulation of post-translational modifications (PTMs). Furthermore, we also want to investigate what effect on the enzyme activity such an accumulation would have. We will particularly focus on glycation, which is a PTM through non-enzymatic reactions between the carbonyl groups (e.g., of methylglyoxal (MGO) or glyoxal (GO)) with amino groups of proteins or other biomolecules. It is already known that the levels of both MGO and GO increase with age. For our investigations, we express each domain of the GNE separately, treat them with one of the glycation agents, and determine their activity. We demonstrate that the enzymatic activity of the N-acetylmannosamine kinase (GNE-kinase domain) decreases dramatically after glycation with MGO or GO—with a remaining activity of 13% ± 5% (5 mM MGO) and 22% ± 4% (5 mM GO). Whereas the activity of the UDP-N-acetylglucosamine 2-epimerase (GNE-epimerase domain) is only slightly reduced after glycation—with a remaining activity of 60% ± 8% (5 mM MGO) and 63% ± 5% (5 mM GO).